Complementation of normal subgroups : in finite groups - Kirtland, Joseph (De Gruyter, 2017)
Starting with the Schur-Zassenhaus theorem, this monograph documents a wide variety of results concerning complementation of normal subgroups in finite groups. The contents cover a wide range of material from reduction theorems and subgroups in the derived and lower nilpotent series to abelian normal subgroups and formations. ContentsPrerequisitesThe Schur-Zassenhaus theorem: A bit of history and motivationAbelian and minimal normal subgroupsReduction theoremsSubgroups in the chief series, derived series, and lower nilpotent seriesNormal subgroups with abelian sylow subgroupsThe formation generationGroups with specific classes of subgroups complemented.